2012
DOI: 10.3390/md10122912
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Structure Elucidation and Total Synthesis of Lajollamide A from the Marine Fungus Asteromyces cruciatus

Abstract: The marine-derived filamentous fungus Asteromyces cruciatus 763, obtained off the coast of La Jolla, San Diego, USA, yielded the new pentapeptide lajollamide A (1), along with the known compounds regiolone (2), hyalodendrin (3), gliovictin (4), 1N-norgliovicitin (5), and bis-N-norgliovictin (6). The planar structure of lajollamide A (1) was determined by Nuclear Magnetic Resonance (NMR) spectroscopy in combination with mass spectrometry. The absolute configuration of lajollamide A (1) was unambiguously solved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 39 publications
(44 reference statements)
0
28
0
Order By: Relevance
“…that was collected in the Bahamas islands), yielded a novel lumazine peptide, penilumamide (179) [83]. Application of OSMAC (one strain-many compounds) methodology to Asteromyces cruciatus 763, isolated from an unidentified decaying green alga (La Jolla shore, San Diego), resulted in the isolation of the pentapeptide lajollamide A (180) and the absolute configuration was solved by total synthesis [84]. The OSMAC approach was based on cultures of the fungus in media derived from the basic components of the Czapek-Dox broth, with glucose as the carbon source, which was either supplemented with cofactors or contained solely the amino acids Arg, Asn, and Glu as a nitrogen source instead of NaNO 3 to afford a good variety of known metabolites and previously unknown compound 180.…”
Section: Nitrogenated Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…that was collected in the Bahamas islands), yielded a novel lumazine peptide, penilumamide (179) [83]. Application of OSMAC (one strain-many compounds) methodology to Asteromyces cruciatus 763, isolated from an unidentified decaying green alga (La Jolla shore, San Diego), resulted in the isolation of the pentapeptide lajollamide A (180) and the absolute configuration was solved by total synthesis [84]. The OSMAC approach was based on cultures of the fungus in media derived from the basic components of the Czapek-Dox broth, with glucose as the carbon source, which was either supplemented with cofactors or contained solely the amino acids Arg, Asn, and Glu as a nitrogen source instead of NaNO 3 to afford a good variety of known metabolites and previously unknown compound 180.…”
Section: Nitrogenated Compoundsmentioning
confidence: 99%
“…(strain no. 6580), associated with a red algal Polysiphonia species (Baltic Sea, Germany), was cultured to produce 11 new botryane sesquiterpenoids(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)…”
mentioning
confidence: 99%
“…Compounds 2-14 were identified as 1-hydroxyeremophil-7(11), 9(10)-di-en-8-one (2) (Sørensen et al 2007), warburgiadione (3) (Yamakawa et al 1979), ere-mofortine A (4) (Moreau et al 1980), 1b-hydroxypetasol (5) (Le et al 2013), 3b-hydroxy-7bH-eremophil-1(2),9(10),11(12)-trien-8-one (6) (Lin et al 2014), 1-ace-tyl-b-carboline (7) (Zhou et al 1998), regiolone (8) (Gulder et al 2012), 2-oxosk-atole (9) (Hoenicke et al 2002), tyrosol (10) (Wang et al 2009), 1-phenyl-1,2-et-hanediol (11) (Zhao et al 2006), α-acetylorcinol (14) (Nukina & Marumo 1977) by comparison of the NMR data with literature ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The planar structure of the antimicrobial lajollamide A 48 ( Figure 7.22), a cyclopentapeptide isolated from marine fungus Asteromyces cruciatus, was determined by NMR spectroscopy in combination with mass spectrometry but the absolute configuration was unambiguously solved by total synthesis [56]. This synthetic sequence provided three additional unnatural diastereomers and showed that the unexpected acid-mediated epimerization of leucine units in the lajollamide framework can be a danger in misassigning natural products structure when elucidated by spectroscopic methods alone.…”
Section: Stereochemistrymentioning
confidence: 99%